Neuroblastoma presenting as hip pain and skull prominence in a child - Hewitt, Hunter R. (Radiol Case Rep, 2019)
Neuroblastoma is a common cancer in children especially those under 5-years old, however they can have varied presentations that may make diagnosis difficult. Neuroblastoma is not usually high on a clinician's differential for a child's gait dysfunction. We describe a case of a 6-year-old female who presented to the Emergency Department for new onset right hip pain. She had associated gait disturbance and pain with ambulation as well as a new lump on her right parietal skull. An MRI of the brain, lumbar spine, and pelvis revealed the diagnosis of a left adrenal neuroblastoma that had metastasized to the femur, the lumbar spine, and the skull. This case shows the importance of early suspicion of malignancy in a patient with seemingly disparate symptoms to ensure early intervention.